The feasibility and efficacy of pedicle fixation by the Wiltse approach in the thoracic spine - Hao, Lu; Xiang, Yufeng; Liu, Junhui (Frontiers in Surgery, 2024)
Study design Retrospective Cohort Study. Objectives To explore the feasibility and assess the efficacy of pedicle fixation with the Wiltse approach in the thoracic spine. Summary of background data The current application of Wiltse approach is mainly practiced in the lumbar and thoracolumbar spines. Its application in the thoracic spine, however, has received little attention, especially in cases that requires only pedicel screw fixation without spinal decompression. Methods The study analyzed the clinical records of consecutive patients with thoracic diseases who underwent pedicle fixation with either Wiltse or the conventional transmuscular approach (Wiltse group: 60 cases; Transmuscular group: 48 cases). Perioperative parameters, Visual Analogue Scale (VAS) scores, accuracy of pedicle screw placement, dead space between the muscles, Magnetic Resonance Imaging (MRI) appearance, electrophysiological changes in the multifidus muscle were compared between the two groups. Results Compared with the transmuscular group, the Wiltse group was significantly better in blood loss and postoperative VAS scores. No difference was observed in incision length, operation time, and hospital stay. The dead space between the muscle cross-sectional region in the transmuscular group was 315 ± 53 mm2, and no dead space was found in the Wiltse group. On MRI images, the multifidus cross-sectional area (CSA) in the Wiltse group between the preoperative period and the last follow-up reduced by only 10.1%, while transmuscular group showed 46.1% CSA reduction. Electrophysiologically, the median frequency slope of the transmuscular group grew by 47.8% with average amplitude reduced by 16.4% between the preoperative period and 12-month postoperative. Conclusion The Wiltse approach for pedicle fixation in the thoracic spine is a feasible and effective treatment, with fewer traumas and reliable clinical results. In particular, the Wiltse approach reduces postoperative dead space between the muscles and causes less atrophy in the multifidus muscle.